Cat-eyed snake (Genus: Boiga) bites in Sri Lanka: First authentic case series. (15th March 2023) - Rathnayaka, R.M.M.K. Namal; Ranathunga, P.E. Anusha Nishanthi; Silva, M.L.I. De; Abeyrathna, Y.N.M.P.; Kularatne, S.A.M.
Abstract: Cat snakes (Genus: Boiga ) are considered to be of lesser medical important in Sri Lanka, as their bites are known to cause only mild local effects such as local pain and swelling at the site of the bite. Five species of cat snakes are found in Sri Lanka, of which three are endemic. They are widely distributed all over the country. Out of seven cases of cat snake bites, including six adults and one child, five developed only mild local effects and two did not have any symptoms. Any of them did not develop systemic manifestations. The snakes responsible were the Sri Lanka cat snake ( Boiga ceylonensis ), Forsten's cat snake ( Boiga forsteni ), and also Ranawana's cat snake ( Boiga ranawanei ) which is the first report in Sri Lanka. Graphical abstract: Image 1 Highlights: There are 5 species of cat snakes ( Boiga spp.) in Sri Lanka. They are lesser medically important snakes. These bites cause mild local effects only. In this series, 7 authentic cases of Boiga bites are presented.